2020
DOI: 10.1080/02827581.2020.1843702
|View full text |Cite
|
Sign up to set email alerts
|

Towards gender equality in family forestry: building self-efficacy together with other female forest owners

Abstract: The share of women among forest owners is growing in the traditionally masculine family forest sector. The present study continues the research on women who own forest in the Nordic setting. The focus is on the behaviour and role of rural female forest owners in Finland, as well as on the benefits of peer learning when building self-efficacy as a forest owner. The qualitative data consist of interviews with female forest owners, peer-learning group observations and feedback. The studied female forest owners wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Follo (2008) reported that, in Norway, women forest owners felt less confident and less knowledgeable in forestry than males. Similar results were also found in Finland (Hamunen et al 2020). In the US, Markowski-Lindsay et al (2020) found out that women forest owners felt less confident, less prepared and less financially capable related to topics of land use when comparing to men.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Follo (2008) reported that, in Norway, women forest owners felt less confident and less knowledgeable in forestry than males. Similar results were also found in Finland (Hamunen et al 2020). In the US, Markowski-Lindsay et al (2020) found out that women forest owners felt less confident, less prepared and less financially capable related to topics of land use when comparing to men.…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, women forest owner networks have been formed in Sweden (Lidestav and Andersson 2011), which have been found to increase member involvement and confidence in forestry activities (Lidestav and Andersson 2011). Similar networks are found in Finland, Norway and the US (Brandth et al 2004;Redmore and Tynon 2010;Ma et al 2012;Huff 2017;Hamunen et al 2020). However, the results of the women-only activities are mixed.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, based on the analysis of our experiment, it can also be concluded that gender alone does not represent a successful market segmentation base among forest owners, even though female forest owners are often discussed as one forest owner group (e.g. Follo et al 2017, Hamunen et al 2020. From the marketing perspective, it is important not to treat them as a group of homogeneous consumers with similar values and objectives concerning their forest management.…”
Section: Discussionmentioning
confidence: 80%
“…For example, being old, male, and rural-oriented had a weakening effect. Since the numbers of female (Hamunen et al 2020 ) as well as non-resident or urban forest owners are increasing (Nordlund and Westin 2011 ; Eggers et al 2014 ), there are growing opportunities to integrate nature conservation into forest management decisions. This changing ownership structure, however, is accompanied by an increase of forest owners with little knowledge and interest in forest management (Weiss et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%